2013
DOI: 10.1002/bit.24776
|View full text |Cite
|
Sign up to set email alerts
|

Optimized signal peptides for the development of high expressing CHO cell lines

Abstract: Recombinant biotherapeutic proteins such as monoclonal antibodies are mostly produced in Chinese hamster ovary (CHO) cells and pharmaceutical companies are interested in an appropriate platform technology for the development of large-scale production processes. A major aim of our study was therefore to improve the secretion efficiency of a recombinant biotherapeutic antibody by optimizing signal peptides. Reporter molecules such as gaussia and vargula luciferase or secreted alkaline phosphatase are frequently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
105
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(115 citation statements)
references
References 29 publications
6
105
1
Order By: Relevance
“…These higher yields are mainly attributed to increased viable cell concentrations (Wurm 2004), but remarkable progress in the improvement of specific production rates were recently reported. For instance, the specific production rate of recombinant cell lines reaches around 50 pg/cell/day (Butler and MenesesAcosta 2012), or around 90 pg/cell/day (Kober et al 2013). However, a plasma cell can secrete several thousands of immunoglobulin M molecules (Randall et al 1992), indicating that a 2.5-12-fold increase in specific productivity is possible (Khan and Schroder 2008).…”
Section: Introductionmentioning
confidence: 99%
“…These higher yields are mainly attributed to increased viable cell concentrations (Wurm 2004), but remarkable progress in the improvement of specific production rates were recently reported. For instance, the specific production rate of recombinant cell lines reaches around 50 pg/cell/day (Butler and MenesesAcosta 2012), or around 90 pg/cell/day (Kober et al 2013). However, a plasma cell can secrete several thousands of immunoglobulin M molecules (Randall et al 1992), indicating that a 2.5-12-fold increase in specific productivity is possible (Khan and Schroder 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Present through the majority of the parts of the secondary structure, A signal peptide is a short peptide (5-30 amino acids long) that exists at the N-terminal of most of the newly synthesized proteins, which are destined towards RMS distances from planarity file the secretory pathways (Blobel and Dobbertein, 1975). Signal peptides are extremely heterogeneous and many prokaryotic and eukaryotic signal peptides are functionally interchangeable even between different species; however, the efficiency of protein secretion is strongly determined by the signal peptide (Kober et al, 2013;Von Heijne, 1985). SignalP analysis showed that At-βgal-NP_001154292 is not a secretory protein, which is the characterization of βgal.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the practicability of applying growth factors, either in form of recombinant proteins or by means of gene therapy encoding an exogenous gene on a plasmid (Feichtinger et al, 2014;Kempen et al, 2010;Koh et al, 2008;Sood et al, 2012). Recombinant proteins used in therapeutic approaches generally show a short half-life at the target site (Alt et al, 2009;Sandhu, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The secretion of proteins can be a limiting step if the native protein secretion signal is weak. The different potencies of secretion signals to drive protein secretion can be related to their amino acid composition (Futatsumori-Sugai and Tsumoto, 2010;Klatt and Konthur, 2012;Knappskog et al, 2007;Kober et al, 2013;Wen et al, 2011;Zhang et al, 2005). Based on this, the present study was expanded by the addition of screening and modification of protein secretion signals in order to identify signal peptide candidates with beneficial activity for subsequent exchange of the native BMP-2 protein secretion sequence.…”
Section: Introductionmentioning
confidence: 99%